Changes in Morphometric Parameters of the Gastric Mucosa under the Influence of Polypharmacy in 3-Month-Old Purebred Male Rats - Norbekovich, Toshmamatov Bakhtiyor; Eshmamatovna , Djumanova Nargiza; Xomidovna , Axmatova Farxunda; Sirojiddinovna , Sirojiddinova Munojat (American Journal of Bioscience and Clinical Integrity, 2025)
Although treating patients with complex medical problems with the right medications can improve clinical outcomes, quality of life, and life expectancy, the risk of adverse drug reactions due to polypharmacy increases, in some cases leading to hospitalization and even death. Therefore, it is critical to have systems in place to ensure that medications are only started when indicated, that patients are fully informed of the benefits and potential complications of treatment, and that patients are regularly reviewed to ensure compliance with their medication regimen.